IMPLEMENTATION AND OPTIMIZATION OF PACKAGING TECHNOLOGIES IN THE TRANSPORT LOGISTICS SECTOR - Bunyod Yuldoshov Tirkashevich, Aliqulov G'olibjon Serzod o'g'li (International Journal of Literature and Language Studies, 2026)
The transport and logistics sector has both scientific and practical significance in ensuring the safe delivery and damage-free storage of goods. Packaging technologies create effective practical conditions for maintaining the quality and integrity of cargo; they enhance operational efficiency, optimize costs, and facilitate more effective and flexible collaboration with couriers. This article provides technical assessments and literary and practical recommendations on control technologies in transport and logistics processes, considering mid-level reasoning, randomness, planetary processes, and agricultural issues that influence the selection of key literature and its appropriate processing.